2011
DOI: 10.1093/treephys/tpr058
|View full text |Cite
|
Sign up to set email alerts
|

Water loss regulation in mature Hevea brasiliensis: effects of intermittent drought in the rainy season and hydraulic regulation

Abstract: Effects of soil and atmospheric drought on whole-tree transpiration (E(T)), leaf water potential (Ψ(L)) and whole-tree hydraulic conductance (K(T)) were investigated in mature rubber trees (Hevea brasiliensis, clone RRIM 600) during the full canopy stage in the rainy season in a drought-prone area of northeast Thailand. Under well-watered soil conditions, transpiration was tightly regulated in response to high evaporative demand, i.e., above reference evapotranspiration (ET(0)) ~2.2 mm day(-1) or maximum vapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…Rubber plantations are much bigger water consumers than native rain forests in this period (Figure 2). The rubber tree (Hevea brasiliensis) is an exotic species originating in the humid Amazon and has large xylem vessels to gain competitive advantages under well-watered conditions [Ayutthaya et al, 2011]. By contrast, the rain forest trees studied here adapt to the seasonally dry environments through long-term evolution and are less sensitive to drought with small xylem vessels (Z.-H. Tan, unpublished data, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Rubber plantations are much bigger water consumers than native rain forests in this period (Figure 2). The rubber tree (Hevea brasiliensis) is an exotic species originating in the humid Amazon and has large xylem vessels to gain competitive advantages under well-watered conditions [Ayutthaya et al, 2011]. By contrast, the rain forest trees studied here adapt to the seasonally dry environments through long-term evolution and are less sensitive to drought with small xylem vessels (Z.-H. Tan, unpublished data, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to this, in the Asian mainland, a much more pronounced and prolonged dry period (including, e.g., drops in soil moisture to 10%) goes along with more complete and homogeneous leaf shedding, which consequently manifests itself in larger reductions of rubber tree water use compared to fully leaved conditions (Isarangkool Na Ayutthaya et al, 2011;Kobayashi et al, 2014;Sopharat et al, 2014). In our study area and period, the dry season was not very pronounced (precipitation events at least once a week), and leaf shedding on rubber trees was not complete (maximum 70% shedding based on visual assessment), relatively short-term (several days to few weeks), successively (not simultaneously even in neighbouring stands), and highly variable at small scales (shedding and nonshedding trees occurred within single plots).…”
Section: Patterns and Controls Of Rubber Tree Water Usementioning
confidence: 90%
“…This raises concerns regarding biodiversity and the carbon budget (Barnes et al, 2014;Kotowska, Leuschner, Triadiati, Meriem, & Hertel, 2015), but also with regard to the integrity of the hydrological cycle (Ziegler et al, 2009). Sap flux measurements on rubber trees in Cambodia and Thailand resulted in much lower transpiration estimates than the evapotranspiration values cited above, but rates were still relatively high (Isarangkool Na Ayutthaya et al, 2011;Kobayashi et al, 2014). Likewise, based on studies in southern China, it was proposed that rubber plantations act as "water pumps", and their evapotranspiration exceeds those of nearby natural forests (Tan et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some studies reported that rubber plantations replacing non-forested lands could act as a carbon sinks (Wauters et al, 2008). Further, while eddy covariance measurements in rubber revealed high plantation water use and a large proportion of energy being used to drive evapotranspiration for most of the year (Tan et al, 2011;Giambelluca et al, submitted for publication, hereinafter referred to as submitted manuscript, 2015), the results of sapflow measurements of individual rubber trees showed water use of rubber plantations may not be as high as anticipated (Isarangkool Na Ayutthaya et al, 2011;Carr, 2012;Kobayashi et al, 2014), but these findings might be related to differences in regional climate, geography, physiological adaptations, and measurement method. Of concern to our research, large-scale land use changes to rubber plantations may have important implications for local-to-regional carbon and water balances, but they still remain unclear.…”
Section: Introductionmentioning
confidence: 98%